2020
DOI: 10.1007/s00401-020-02128-8
|View full text |Cite
|
Sign up to set email alerts
|

Truncating mutations in YIF1B cause a progressive encephalopathy with various degrees of mixed movement disorder, microcephaly, and epilepsy

Abstract: N. (2020). Truncating mutations in YIF1B cause a progressive encephalopathy with various degrees of mixed movement disorder, microcephaly, and epilepsy. Acta Neuropathologica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 7 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…In patients 3.1 and 5.1, lack of visual evoked potential was observed even with flash stimulation suggesting retinal dysfunction. Likewise, the patient from family 5 of the recently published study on patients carrying YIF1B mutations also exhibited cortical blindness (AlMuhaizea et al, 2020). Hence, we further explored visual functions in the Yif1b-KO mice.…”
Section: Yif1b-ko Mice Have Deficits Similar To Those Observed In Patients Carrying Yif1b Mutationsmentioning
confidence: 95%
See 1 more Smart Citation
“…In patients 3.1 and 5.1, lack of visual evoked potential was observed even with flash stimulation suggesting retinal dysfunction. Likewise, the patient from family 5 of the recently published study on patients carrying YIF1B mutations also exhibited cortical blindness (AlMuhaizea et al, 2020). Hence, we further explored visual functions in the Yif1b-KO mice.…”
Section: Yif1b-ko Mice Have Deficits Similar To Those Observed In Patients Carrying Yif1b Mutationsmentioning
confidence: 95%
“…Its deletion in mouse neurons leads to GA disorganization (Alterio et al, 2015) and alteration of the dendritic targeting of a specific serotonergic receptor (Carrel et al, 2008). A recent study identified mutations in the YIF1B gene in patients displaying progressive encephalopathy with various degrees of mixed movement disorder, microcephaly and epilepsy (AlMuhaizea et al, 2020). In the current study, we also identified mutations of the YIF1B gene in six families comprising 10 affected patients with neurological deficits that could not be classified by clinicians as a specific pathology, but whose clinical manifestations were close to those observed in Golgipathies.…”
Section: Introductionmentioning
confidence: 99%
“…We performed filtering steps on the WES as described previously 12,13,15‐17 . The analysis yielded a single most plausible candidate, a homozygous missense variant in TBCD (NM_005993.5: c.1712A > G, p.K571R) in family A. Sanger sequencing confirmed complete segregation of the variant within the family (Figure 1(A)).…”
Section: Resultsmentioning
confidence: 99%
“…The sequencing was performed on the Ion Proton™ System (Life Technologies), using Ion PI™ Sequencing 200 Kit v3 with the Ion PI™ Chip Kit v2 (Life Technologies). WES data was filtered and the candidate variants were confirmed by Sanger Sequencing 12,13 . Variants were tested for potential pathogenicity using various prediction algorithms tools 14 …”
Section: Methodsmentioning
confidence: 99%
“…Although YIF1B is known to interact with the serotonin receptor, HTR1A, the identification of further binding partners and the full extent of its involvement in serotonin signaling requires further investigation. A link to signaling pathways via HTR receptors is the likely reason for association of YIF1B mutations with functional changes to specific proteins in neuronal cells, causing encephalopathy, epilepsy and movement disorder [23]. Although serotonin has been linked to cancer, a role for YIF1B in tumorigenesis and cancer progression has not been previously established.…”
Section: Discussionmentioning
confidence: 99%